GG-04 Pathogenic role of SAT1 variants in monogenic lupus. (August 2018) - Zhao, Jian; Deng, Yun; Raj, Prithvi; Wakeland, Edward K; McCurdy, Deborah K; Tsao, Betty P
Abstract : Background: Genetic susceptibility of SLE in general is attributed to the overall risk of multiple common variants that each confers a small effect. However, in few cases, highly penetrant single gene variants have been reported as monogenic forms of SLE. To explore novel risk variants, we carried out whole-exome sequencing to identify underlying monogenic causes from two multiplex families that each family has two boys with childhood onset lupus nephritis. Methods: We sequenced the whole exome of lupus patients and their parents using the Illumina's instrument Hiseq2000. We conducted variant calling and annotation using the Genome Analysis Toolkit GATK and ANNOVAR, respectively. Our findings of exome-seq was confirmed using the Sanger sequencing. Results: Using bioinformatics, we focused only on potential loss-of-function variants. In addition, by using the recessive inheritance model and allele frequency <1% in population as filter, we identified potentially pathogenic variants from the SAT1 gene on chromosome X but not in previously known SLE-associated genes. In each family, we identified an exonic variant in an X-linked gene SAT1 . These two variants presumably lead to the loss-of-function of SAT1. Both variants are inherited in the X-linked recessive pattern and they are extremely rare in the population (absent in >2 00 000 individuals). In one family, the SAT1 frameshift mutation was transmitted from the mother to the two sons affected with SLE but not to the unaffected son. Conclusions: We identified SAT1 as a novel gene associated with monogenic lupus. SAT1 encodes the spermidine/spermine-N 1 -acetyltransferase (SSAT), a rate-limiting enzyme that regulates the catabolism of polyamine. We hypothesize that loss-of-function SAT1 variants may cause dysregulated polyamine homeostasis which confers risk of SLE.